A modified glass fiber liquid nitrogen adsorption material and preparation method thereof
By combining nano-titanium dioxide modified hydroxylated glass fibers with silica aerogels, the modified glass fiber liquid nitrogen adsorption material is solved, and the problem of poor wear resistance of existing liquid nitrogen adsorption materials in ultra-low temperature environments is achieved. Good adsorption and service life.
Patent Information
- Application Number
- CN202411629152.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing liquid nitrogen adsorbent materials have poor wear resistance and short service life in ultra-low temperature environments, which cannot meet the requirements of liquid nitrogen biological containers.
Nanotitanium dioxide modified hydroxylated glass fibers are combined with silica aerogel with a nanopore network structure, and filled in the voids between the glass fibers to form a modified glass fiber liquid nitrogen adsorption material.
It significantly improves the wear resistance and adsorption properties of modified glass fiber liquid nitrogen adsorbent materials, extends the service life, and meets the needs of liquid nitrogen biological containers.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modified glass fiber and low-temperature refrigeration adsorption material, in particular to a modified glass fiber liquid nitrogen adsorption material and a preparation method thereof. Background Art
[0002] In industrial production, liquid nitrogen is obtained by the fractional distillation of compressed liquid air and is used as a deep refrigerant. Due to its chemical inertness, it can directly contact biological tissues and freeze them immediately without destroying biological activity. Therefore, liquid nitrogen has a wide range of uses in rapid freezing and transportation of food, research in low-temperature physics, industrial nitrogen fertilizer production, and aviation low-temperature transportation.
[0003] Liquid nitrogen storage containers are usually composed of an outer liner, an inner liner, insulating materials and other accessories. The insulating material is located between the outer liner and the inner liner, which can maintain the low temperature of the inner liner. In addition, the inner liner needs to be filled with liquid nitrogen adsorption material. On the one hand, it can prevent liquid nitrogen leakage and sample damage caused by container shaking. On the other hand, it also plays the role of adsorbing and fixing liquid nitrogen to prevent liquid nitrogen from evaporating too quickly.
[0004] The existing technology uses aerogel composite ultra-fine glass fiber felt as liquid nitrogen adsorption material, which is applied to aviation liquid nitrogen adsorption containers. However, in the ultra-low temperature environment of liquid nitrogen, aerogel composite ultra-fine glass fiber felt cannot maintain good mechanical properties, so the wear resistance becomes poor, and a lot of debris will be generated after long-term use, and the service life is short.
[0005] Therefore, there is an urgent need to study a liquid nitrogen adsorption material with good wear resistance, adsorption and long service life. Summary of the invention
[0006] To solve the above problems, the object of the present invention is to provide a modified glass fiber liquid nitrogen adsorption material and a preparation method thereof.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] A modified glass fiber liquid nitrogen adsorption material is prepared by using nano-titanium dioxide modified hydroxylated glass fiber and polyethylene glycol as base materials and compounding with silicon dioxide aerogel having a nanoporous network structure, wherein the silicon dioxide aerogel is filled in the gaps between the nano-titanium dioxide modified hydroxylated glass fibers.
[0009] The present invention also includes a method for preparing a modified glass fiber liquid nitrogen adsorption material, comprising the following steps:
[0010] ① In parts by weight, 20 parts of glass fiber are added to 90-110 parts of hydrochloric acid aqueous solution and soaked for 2-4 hours, heated to 60-70°C, allowed to stand for 6-10 hours, filtered, washed with deionized water to a pH of 6-7, and added to 140-200 parts of ethanol to obtain a hydroxylated glass fiber-ethanol solution;
[0011] ② Under stirring, 18 to 20 parts of n-butyl titanate are added dropwise to 90 to 110 parts of ethanol aqueous solution with a mass concentration of 85 to 90%, and the addition speed is controlled to be 1 to 4 ml / 10 seconds. After the addition is completed, 8 to 15 parts of nitric acid are added dropwise thereto, and the addition speed is controlled to be 2 to 5 ml / 10 seconds. After the addition is completed, stirring is continued for 10 to 20 minutes to obtain a mixed solution, which is added to the hydroxylated glass fiber-ethanol solution obtained in step ①, the temperature is raised to 40 to 50° C., stirred for 20 to 40 minutes, allowed to stand for 2 to 4 hours, filtered, and the obtained solid is washed with deionized water to a pH value of 6 to 7, and then washed with anhydrous ethanol for 3 to 5 times, and dried to obtain nano-titanium dioxide modified hydroxylated glass fiber;
[0012] ③ Add 25-30 parts of tetraethyl orthosilicate to 70-80 parts of 70-75% ethanol aqueous solution, adjust the pH value to 2-4 with hydrochloric acid, stir for 0.5-1 hour, heat to 40-50° C. and stand for 2-4 hours, adjust the pH to 6-8 with aqueous ammonia, add 15-25 parts of the nano-titanium dioxide modified hydroxylated glass fiber obtained in step ② and 1-5 parts of polyethylene glycol, stir for 10-20 minutes, add 300-320 parts of hexamethyldisilazane ethanol solution, stir for 10-20 minutes, heat to 50-60° C. and stand for 4-8 hours, filter, and dry the obtained solid with a supercritical carbon dioxide drying device to obtain a modified glass fiber liquid nitrogen adsorption material;
[0013] The mass concentration of hexamethyldisilazane in the hexamethyldisilazane ethanol solution is 8-14%.
[0014] Preferably, the supercritical carbon dioxide drying temperature is 50-60° C. and the pressure is 14-15 MPa.
[0015] Preferably, the mass concentration of the aqueous hydrochloric acid solution in step ① is 0.5~1 mol / L.
[0016] Preferably, in step ③, the mass concentration of hydrochloric acid is 25-30%, and the mass concentration of ammonia water is 10-15%.
[0017] Preferably, the molecular weight of the polyethylene glycol is 1000-4000 Daltons.
[0018] The invention also includes application of a modified glass fiber liquid nitrogen adsorption material as a liquid nitrogen storage and adsorption material.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] The modified glass fiber liquid nitrogen adsorption material of the present invention has good wear resistance, good adsorption and long service life, and can meet the requirements of liquid nitrogen biological containers. The modified glass fiber liquid nitrogen adsorption material of the present invention first reacts n-butyl titanate with glass fiber to obtain nano titanium dioxide modified glass fiber, and titanium dioxide is attached to the surface of the glass fiber to increase the strength of the glass fiber surface, thereby significantly improving the wear resistance of the glass fiber and preventing the generation of debris; secondly, under acidic heating conditions, a large number of hydroxyl groups will be generated on the surface of the glass fiber, and these hydroxyl groups can react and cross-link when contacting with the hydroxyl groups on the surface of the silica aerogel, thereby enhancing the mechanical strength of the glass fiber, further improving the wear resistance of the glass fiber, and extending the service life; in addition, the present invention also adds polyethylene glycol, which has good molecular flexibility, and can not only enhance the low temperature resistance of the liquid nitrogen adsorption material, but also enhance the mechanical strength of the glass fiber. DETAILED DESCRIPTION
[0021] The object of the present invention is to provide a modified glass fiber liquid nitrogen adsorption material and a preparation method thereof. The present invention is further described below in conjunction with specific embodiments.
[0022] Example 1 A method for preparing a modified glass fiber liquid nitrogen adsorption material comprises the following steps:
[0023] ① Add 20 kg of glass fiber to 90 kg of 1 mol / L hydrochloric acid aqueous solution and soak for 2 hours, heat to 70 ° C, stand for 6 hours, filter, wash with deionized water to a pH of 6, add to 140 kg of ethanol to obtain a hydroxylated glass fiber-ethanol solution;
[0024] ② Under stirring, 18 kg of n-butyl titanate was added dropwise to 90 kg of ethanol aqueous solution with a mass concentration of 85%, and the dropping speed was controlled to 1 ml / 10 seconds. After the dropping was completed, 8 kg of nitric acid was added dropwise thereto, and the dropping speed was controlled to 2 ml / 10 seconds. After the dropping was completed, stirring was continued for 10 minutes to obtain a mixed solution, which was added to the hydroxylated glass fiber-ethanol solution obtained in step ①, heated to 40°C, stirred for 20 minutes, allowed to stand for 2 hours, filtered, and the obtained solid was washed with deionized water to a pH value of 6, and then washed with anhydrous ethanol for 3 times, and dried to obtain nano-titanium dioxide modified hydroxylated glass fiber;
[0025] ③ Add 25kg of tetraethyl orthosilicate to 70kg of 70% ethanol aqueous solution, adjust the pH value to 2 with 25% hydrochloric acid, stir for 0.5 hour, heat to 40°C and stand for 2 hours, adjust the pH to 6 with 10% ammonia water, add 15kg of nano-titanium dioxide modified hydroxylated glass fiber obtained in step ② and 1kg of polyethylene glycol with a molecular weight of 4000 Daltons, stir for 10 minutes, add 300kg of hexamethyldisilazane ethanol solution, stir for 10 minutes, heat to 50°C and stand for 4 hours, filter, and dry the obtained solid with a supercritical carbon dioxide drying device to obtain a modified glass fiber liquid nitrogen adsorption material; the supercritical carbon dioxide drying temperature is 50°C and the pressure is 14MPa;
[0026] The mass concentration of hexamethyldisilazane in the hexamethyldisilazane ethanol solution is 8%.
[0027] Example 2 A method for preparing a modified glass fiber liquid nitrogen adsorption material comprises the following steps:
[0028] ① Add 20 kg of glass fiber to 110 kg of 0.5 mol / L hydrochloric acid aqueous solution and soak for 4 hours, heat to 60 ° C, stand for 10 hours, filter, wash with deionized water to pH 7, add to 200 kg of ethanol to obtain hydroxylated glass fiber-ethanol solution;
[0029] ② Under stirring, 20 kg of n-butyl titanate was added dropwise to 110 kg of 90% ethanol aqueous solution, the dropping speed was controlled to 4 ml / 10 seconds, and 15 kg of nitric acid was added dropwise thereto, the dropping speed was controlled to 5 ml / 10 seconds, and the stirring was continued for 20 minutes after the dropping was completed to obtain a mixed solution, which was added to the hydroxylated glass fiber-ethanol solution obtained in step ①, the temperature was raised to 50° C., stirred for 40 minutes, allowed to stand for 4 hours, filtered, and the obtained solid was washed with deionized water to a pH value of 7, and then washed with anhydrous ethanol 5 times, and dried to obtain nano-titanium dioxide modified hydroxylated glass fiber;
[0030] ③ Add 30kg of tetraethyl orthosilicate to 80kg of 75% ethanol aqueous solution, adjust the pH value to 4 with 30% hydrochloric acid, stir for 1 hour, heat to 50°C and stand for 4 hours, adjust the pH to 8 with 15% ammonia water, add 25kg of the nano-titanium dioxide modified hydroxylated glass fiber obtained in step ② and 5kg of polyethylene glycol with a molecular weight of 1000 Daltons, stir for 20 minutes, add 320kg of hexamethyldisilazane ethanol solution, stir for 20 minutes, heat to 60°C and stand for 8 hours, filter, and dry the obtained solid with a supercritical carbon dioxide drying device to obtain a modified glass fiber liquid nitrogen adsorption material; the supercritical carbon dioxide drying temperature is 60°C and the pressure is 15MPa;
[0031] The mass concentration of hexamethyldisilazane in the hexamethyldisilazane ethanol solution is 14%.
[0032] Example 3 A method for preparing a modified glass fiber liquid nitrogen adsorption material comprises the following steps:
[0033] ① Add 20 kg of glass fiber to 100 kg of 0.6 mol / L hydrochloric acid aqueous solution and soak for 2.5 hours, heat to 65 ° C, stand for 7 hours, filter, wash with deionized water to a pH of 6.5, add to 150 kg of ethanol to obtain a hydroxylated glass fiber-ethanol solution;
[0034] ② Under stirring, 18.5 kg of n-butyl titanate was added dropwise to 100 kg of ethanol aqueous solution with a mass concentration of 88%, and the dropping speed was controlled to 2 ml / 10 seconds. After the dropping was completed, 10 kg of nitric acid was added dropwise thereto, and the dropping speed was controlled to 4 ml / 10 seconds. After the dropping was completed, stirring was continued for 12 minutes to obtain a mixed solution, which was added to the hydroxylated glass fiber-ethanol solution obtained in step ①, heated to 42° C., stirred for 25 minutes, allowed to stand for 2.5 hours, filtered, and the obtained solid was washed with deionized water to a pH value of 6.5, then washed 4 times with anhydrous ethanol, and dried to obtain nano-titanium dioxide modified hydroxylated glass fiber;
[0035] ③ Add 26kg of tetraethyl orthosilicate to 72kg of 72% ethanol aqueous solution, adjust the pH value to 2.5 with 28% hydrochloric acid, stir for 40 minutes, heat to 42°C and stand for 2.5 hours, adjust the pH to 6.5 with 12% ammonia water, add 18kg of nano-titanium dioxide modified hydroxylated glass fiber obtained in step ② and 2kg of polyethylene glycol with a molecular weight of 2000 Daltons, stir for 12 minutes, add 305kg of hexamethyldisilazane ethanol solution, stir for 12 minutes, heat to 52°C and stand for 5 hours, filter, and dry the obtained solid with a supercritical carbon dioxide drying device to obtain a modified glass fiber liquid nitrogen adsorption material; the supercritical carbon dioxide drying temperature is 55°C and the pressure is 14.5MPa;
[0036] The mass concentration of hexamethyldisilazane in the hexamethyldisilazane ethanol solution is 9%.
[0037] Example 4 A method for preparing a modified glass fiber liquid nitrogen adsorption material comprises the following steps:
[0038] ① Add 20 kg of glass fiber to 105 kg of 0.9 mol / L hydrochloric acid aqueous solution and soak for 3 hours, heat to 65 ° C, let stand for 7 hours, filter, wash with deionized water to a pH of 6.5, add to 160 kg of ethanol to obtain a hydroxylated glass fiber-ethanol solution;
[0039] ② Under stirring, 19 kg of n-butyl titanate was added dropwise to 105 kg of ethanol aqueous solution with a mass concentration of 86%, and the dropping speed was controlled to 3 ml / 10 seconds. After the dropping was completed, 12 kg of nitric acid was added dropwise thereto, and the dropping speed was controlled to 3 ml / 10 seconds. After the dropping was completed, stirring was continued for 14 minutes to obtain a mixed solution, which was added to the hydroxylated glass fiber-ethanol solution obtained in step ①, heated to 42° C., stirred for 35 minutes, allowed to stand for 3 hours, filtered, and the obtained solid was washed with deionized water to a pH value of 6.5, then washed 4 times with anhydrous ethanol, and dried to obtain nano-titanium dioxide modified hydroxylated glass fiber;
[0040] ③ Add 28kg of tetraethyl orthosilicate to 78kg of 74% ethanol aqueous solution, adjust the pH value to 3 with 26% hydrochloric acid, stir for 50 minutes, heat to 46°C and stand for 3.5 hours, adjust the pH to 6.2 with 14% ammonia water, add 22kg of the nano-titanium dioxide modified hydroxylated glass fiber obtained in step ② and 4kg of polyethylene glycol with a molecular weight of 2500 Daltons, stir for 15 minutes, add 305kg of hexamethyldisilazane ethanol solution, stir for 18 minutes, heat to 58°C and stand for 7 hours, filter, and dry the obtained solid with a supercritical carbon dioxide drying device to obtain a modified glass fiber liquid nitrogen adsorption material; the supercritical carbon dioxide drying temperature is 56°C and the pressure is 14.2MPa;
[0041] The mass concentration of hexamethyldisilazane in the hexamethyldisilazane ethanol solution is 12%.
[0042] Example 5 A method for preparing a modified glass fiber liquid nitrogen adsorption material comprises the following steps:
[0043] ① Add 20 kg of glass fiber to 108 kg of 0.8 mol / L hydrochloric acid aqueous solution and soak for 3.5 hours, heat to 64 ° C, stand for 7 hours, filter, wash with deionized water to a pH of 6.8, and add to 160 kg of ethanol to obtain a hydroxylated glass fiber-ethanol solution;
[0044] ② Under stirring, 19.5 kg of n-butyl titanate was added dropwise to 98 kg of ethanol aqueous solution with a mass concentration of 86%, and the dropping speed was controlled to 2 ml / 10 seconds. After the dropping was completed, 10 kg of nitric acid was added dropwise thereto, and the dropping speed was controlled to 4 ml / 10 seconds. After the dropping was completed, stirring was continued for 16 minutes to obtain a mixed solution, which was added to the hydroxylated glass fiber-ethanol solution obtained in step ①, heated to 44° C., stirred for 35 minutes, allowed to stand for 2.5 hours, filtered, and the obtained solid was washed with deionized water to a pH value of 6.5, then washed 4 times with anhydrous ethanol, and dried to obtain nano-titanium dioxide modified hydroxylated glass fiber;
[0045] ③ Add 26kg of tetraethyl orthosilicate to 74kg of 72% ethanol aqueous solution, adjust the pH value to 2.5 with 26% hydrochloric acid, stir for 40 minutes, heat to 42°C and stand for 3 hours, adjust the pH to 7.5 with 12% ammonia water, add 22kg of the nano-titanium dioxide modified hydroxylated glass fiber obtained in step ② and 3kg of polyethylene glycol with a molecular weight of 3000 Daltons, stir for 18 minutes, add 312kg of hexamethyldisilazane ethanol solution, stir for 15 minutes, heat to 56°C and stand for 5 hours, filter, and dry the obtained solid with a supercritical carbon dioxide drying device to obtain a modified glass fiber liquid nitrogen adsorption material; the supercritical carbon dioxide drying temperature is 54°C and the pressure is 14.2MPa;
[0046] The mass concentration of hexamethyldisilazane in the hexamethyldisilazane ethanol solution is 10%.
[0047] Example 6 A method for preparing a modified glass fiber liquid nitrogen adsorption material comprises the following steps:
[0048] ① Add 20 kg of glass fiber to 100 kg of 0.7 mol / L hydrochloric acid aqueous solution and soak for 3 hours, heat to 65 ° C, stand for 8 hours, filter, wash with deionized water to a pH of 6.5, add to 160 kg of ethanol to obtain a hydroxylated glass fiber-ethanol solution;
[0049] ② Under stirring, 19 kg of n-butyl titanate was added dropwise to 100 kg of 90% ethanol aqueous solution, the dropping speed was controlled to 3 ml / 10 seconds, and 10 kg of nitric acid was added dropwise thereto after the dropping was completed, the dropping speed was controlled to 3 ml / 10 seconds, and the stirring was continued for 15 minutes after the dropping was completed to obtain a mixed solution, which was added to the hydroxylated glass fiber-ethanol solution obtained in step ①, the temperature was raised to 45° C., stirred for 30 minutes, allowed to stand for 3 hours, filtered, and the obtained solid was washed with deionized water to a pH value of 6.5, and then washed with anhydrous ethanol 4 times, and dried to obtain nano-titanium dioxide modified hydroxylated glass fiber;
[0050] ③ Add 28kg of tetraethyl orthosilicate to 75kg of 72% ethanol aqueous solution, adjust the pH value to 3 with 28% hydrochloric acid, stir for 45 minutes, heat to 45°C and stand for 3 hours, adjust the pH to 7 with 14% ammonia water, add 20kg of the nano-titanium dioxide modified hydroxylated glass fiber obtained in step ② and 3kg of polyethylene glycol with a molecular weight of 2500 Daltons, stir for 15 minutes, add 310kg of hexamethyldisilazane ethanol solution, stir for 15 minutes, heat to 55°C and stand for 6 hours, filter, and dry the obtained solid with a supercritical carbon dioxide drying device to obtain a modified glass fiber liquid nitrogen adsorption material; the supercritical carbon dioxide drying temperature is 55°C and the pressure is 14.8MPa;
[0051] The mass concentration of hexamethyldisilazane in the hexamethyldisilazane ethanol solution is 10%.
[0052] The modified glass fiber liquid nitrogen adsorption materials obtained in Examples 1 to 6 of the present invention were tested for density and porosity. The results are shown in Table 1, wherein the density was tested in accordance with GB / T 41063-2021 for the determination of glass fiber density, and the porosity was tested in accordance with T / CSTM 00553-2022 for the determination of porosity of lightweight porous materials.
[0053] Table 1 Density and porosity test results
[0054]
[0055] It can be seen from the results in Table 1 that the modified glass fiber liquid nitrogen adsorption material of the present invention has a relatively small density and a relatively high porosity, and is convenient for being placed in a nitrogen insulation material to adsorb nitrogen.
[0056] Application test
[0057] The modified glass fiber liquid nitrogen adsorption materials obtained in Examples 1 to 6 of the present invention were subjected to a comparative experiment on the adsorption and evaporation of liquid nitrogen. The experimental process is as follows:
[0058] 1000 g of the modified glass fiber liquid nitrogen adsorption material obtained in Examples 1 to 6 were weighed and placed in 8L low-temperature insulation barrels of the same model. At the same time, a similar empty barrel was used for a comparative experiment. 7.5 L of liquid nitrogen was added to the insulation barrel. After standing for 1 hour, the weight was weighed on an electronic scale. Then, the small mouth of the 8L low-temperature insulation barrel was opened to ensure that the small mouth of each barrel was the same size (recorded as the initial moment). The change in weight over time was recorded (experimental environment 25° C., relative humidity 70 RH%). The effect of the modified glass fiber liquid nitrogen adsorption material obtained in Examples 1 to 6 on the evaporation rate of liquid nitrogen was calculated. The results are shown in Table 2.
[0059] Table 2 Effect of modified glass fiber liquid nitrogen adsorption material on liquid nitrogen evaporation rate
[0060]
[0061] It can be seen from the results in Table 2 that, under the same opening of the insulation barrel, the modified glass fiber liquid nitrogen adsorption material of the present invention has a good adsorption capacity for nitrogen, which greatly shortens the natural volatilization time of nitrogen, indicating that liquid nitrogen is adsorbed into the micropores by the modified glass fiber liquid nitrogen adsorption material, and the skeleton of the aerogel of the present invention forms a heat insulation barrier for liquid nitrogen, which greatly reduces the evaporation rate of liquid nitrogen.
[0062] After 150 minutes, the low-temperature insulation barrel was opened, and the liquid nitrogen evaporated completely after 2 to 3 hours. It was observed that the modified glass fiber liquid nitrogen adsorption material of the present invention did not produce debris, had good wear resistance, and was in the same state as before being placed in nitrogen, and could be recycled. When in use, the items to be stored at low temperatures could be directly placed in the liquid nitrogen storage container to prevent liquid nitrogen leakage and sample damage caused by container shaking.
Claims
1. A modified glass fiber liquid nitrogen adsorption material, characterized in that: The nano-titanium dioxide modified hydroxylated glass fiber and polyethylene glycol are used as the base material and are compounded with silica aerogel having a nanoporous network structure, wherein the silica aerogel is filled in the gaps between the nano-titanium dioxide modified hydroxylated glass fibers; The modified glass fiber liquid nitrogen adsorption material is prepared according to the following steps: ① In parts by weight, 20 parts of glass fiber are added to 90-110 parts of hydrochloric acid aqueous solution and soaked for 2-4 hours, heated to 60-70°C, allowed to stand for 6-10 hours, filtered, washed with deionized water to a pH of 6-7, and added to 140-200 parts of ethanol to obtain a hydroxylated glass fiber-ethanol solution; ② Under stirring, 18 to 20 parts of n-butyl titanate are added dropwise to 90 to 110 parts of ethanol aqueous solution with a mass concentration of 85 to 90%, and the addition speed is controlled to be 1 to 4 ml / 10 seconds. After the addition is completed, 8 to 15 parts of nitric acid are added dropwise thereto, and the addition speed is controlled to be 2 to 5 ml / 10 seconds. After the addition is completed, stirring is continued for 10 to 20 minutes to obtain a mixed solution, which is added to the hydroxylated glass fiber-ethanol solution obtained in step ①, the temperature is raised to 40 to 50° C., stirred for 20 to 40 minutes, allowed to stand for 2 to 4 hours, filtered, and the obtained solid is washed with deionized water to a pH value of 6 to 7, and then washed with anhydrous ethanol for 3 to 5 times, and dried to obtain nano-titanium dioxide modified hydroxylated glass fiber; ③ Add 25-30 parts of tetraethyl orthosilicate to 70-80 parts of 70-75% ethanol aqueous solution, adjust the pH value to 2-4 with hydrochloric acid, stir for 0.5-1 hour, heat to 40-50° C. and stand for 2-4 hours, adjust the pH to 6-8 with aqueous ammonia, add 15-25 parts of the nano-titanium dioxide modified hydroxylated glass fiber obtained in step ② and 1-5 parts of polyethylene glycol, stir for 10-20 minutes, add 300-320 parts of hexamethyldisilazane ethanol solution, stir for 10-20 minutes, heat to 50-60° C. and stand for 4-8 hours, filter, and dry the obtained solid with a supercritical carbon dioxide drying device to obtain a modified glass fiber liquid nitrogen adsorption material; The mass concentration of hexamethyldisilazane in the hexamethyldisilazane ethanol solution is 8-14%.
2. The modified glass fiber liquid nitrogen adsorption material according to claim 1, characterized in that: The supercritical carbon dioxide drying temperature is 50-60° C. and the pressure is 14-15 MPa.
3. The modified glass fiber liquid nitrogen adsorption material according to claim 1, characterized in that: The mass concentration of the hydrochloric acid aqueous solution in step ① is 0.5~1 mol / L.
4. The modified glass fiber liquid nitrogen adsorption material according to claim 1, characterized in that: In step ③, the mass concentration of hydrochloric acid is 25-30%, and the mass concentration of ammonia water is 10-15%.
5. The modified glass fiber liquid nitrogen adsorption material according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 1000-4000 Daltons.
6. The use of a modified glass fiber liquid nitrogen adsorption material according to claim 1, characterized in that: For liquid nitrogen storage and adsorption.
Citation Information
Patent Citations
Aerogel composite superfine glass fiber cotton felt, preparation method thereof and application of aerogel composite superfine glass fiber cotton felt as liquid nitrogen adsorption material
CN111841486A